Mortality and complication management after surgery for colorectal cancer depending on the DKG minimum amounts for hospital volume. Issue 4 (April 2021) - Diers, Johannes; Baum, Philip; Matthes, Harald; Germer, Christoph-Thomas; Wiegering, Armin
Abstract: Background: The German Cancer Society ("Deutsche Krebsgesellschaft"; DKG) certifies on a volunteer base colorectal cancer centers based on, among other things, minimum operative amounts (at least 30 oncological colon cancer resections and 20 oncological rectal cancer resections per year). In this work, nationwide hospital mortality and death after documented complications ('Failure to Rescue' = FtR) were evaluated depending on the fulfillment of the minimum amounts. Methods: This is a retrospective analysis of the nationwide hospital billing data (DRG data, 2012–2017). Categorization is based on the DKG minimum quantities (fully, partially or not fulfilled). Results: Of 287, 227 patients analyzed, 56.5% were operated in centers that met the DKG minimum amounts. The overall hospital mortality rate was 5.0%. In centers which met the minimum quantities, it was significantly lower (4.3%) than in hospitals which partially (5.7%) or not (6.2%) met the minimum quantities. The risk-adjusted hospital mortality rate for patients in hospitals who meet the minimum amount was 20% lower (OR 0.80; 95% CI [0.74–0.87], p < 0.001). For complications, both surgical and non-surgical, there was an unadjusted and adjusted lower FtR in hospitals that met the minimum amounts (e.g. anastomotic leak: 11.2% vs. 15.6%, p < 0.001; pulmonary artery embolism 21.3% vs. 28.2%, p = 0.001). Conclusion: There is a 1/3 lower mortality and FtR rate after surgery for a colon or rectal cancer in centers fulfilling the DKG minimum amounts. The presented data implicate that there is an urgent need for a nationwide centralization program.